SISTEM INFORMASI GEOGRAFIS INVENTARISASI RUAS JALAN DAN JEMBATAN DI KOTA DENPASAR - Oka Sudana, A.A.K.; Hadi, Daniel (Jurnal Ilmiah Teknik Sipil, 2012)
Denpasar as a rapidly growing city needs good traffic (road ways, bridges and traffic lights) inventory. However, in actual fact, at present the goverment agents in charge are still using graphical data in the form of maps and manual information data (blueprints and paper) which results in various problems. Some of the problems include problems in data storage since the map and information data available at present are saved using paper media which would not last very long and easily damaged, problems in planning the maintenance of road ways, bridges and traffic lights because of the relatively long time spent to check the condition, last maintenance time, and associating acquired data with the maps, which could take half a day (according to the amount of data searched) since the checking of data is done manually and separately (disintegrated) from the information data in the maps. Furthermore, manual data checking has a low level of accuracy, since there could be data skipped in the checking process. To overcome the problem of traffic inventory (road ways, bridges and traffic lights) in Denpasar, a GIS-based System (Geographical Information System) is designed and made in this final project, which could deliver information on road ways, bridges and traffic lights in Denpasar in detail. This system would give solutions to the problems such as digital (softcopy) and integrated map data and information data storage so that the map data will last longer and not easily damaged (not including the condition of force majeure), decision making in planning the maintenance of road ways, bridges and traffic lights could be made faster since the checking of the condition, last maintenance time and map marking is done by the system to the integrated data and takes just a few seconds to complete. Moreover, data checking done by the system will have relatively high accuracy, as there would be no data skipped in the checking process.
Keywords: Denpasar, Inventory, Traffic, Road Ways, Bridges, Traffic Lights, GIS